Recycling and Re-use of Waste Rubber - Forrest, Martin J. (De Gruyter, 2019)
Recycling of rubber materials is necessary from both an environmental and economic perspective. This book describes everything from the world market to the many novel technologies and processes developed for the re-use and recycling of our common rubber materials. Devulcanization, production of rubber crumbs, reprocessing and manufacture of new materials are thoroughly described and discussed.- Resumé vydavatel
Keywords: pryž; recyklace odpadu; rubber; waste recycling; elektronické knihy; monografie; electronic books; monographs